1999
DOI: 10.1073/pnas.96.18.10021
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for proton release during ubihydroquinone oxidation by the bc 1 complex

Abstract: Quinol oxidation by the bc 1 complex of Rhodobacter sphaeroides occurs from an enzyme-substrate complex formed between quinol bound at the Q o site and the iron-sulfur protein (ISP) docked at an interface on cytochrome b. From the structure of the stigmatellin-containing mitochondrial complex, we suggest that hydrogen bonds to the two quinol hydroxyl groups, from Glu-272 of cytochrome b and His-161 of the ISP, help to stabilize the enzyme-substrate complex and aid proton release. Reduction of the oxidized ISP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
255
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(283 citation statements)
references
References 38 publications
(80 reference statements)
26
255
1
1
Order By: Relevance
“…The structures suggest that this occurs through protonation of Glu-272 and rotation of the side chain, followed by dissociation and exit of the H + via the water chain proposed in ref 47 and discussed above ( Figure 7B,C) (49). Since rotation of Glu-272 away from the pocket is required to allow movement to the proximal domain, this would suggest that deprotonation of the semiquinone occurs before oxidation (after step c and before step d above), so that the semiquinone anion moves and donates to heme b L (steps d and e).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The structures suggest that this occurs through protonation of Glu-272 and rotation of the side chain, followed by dissociation and exit of the H + via the water chain proposed in ref 47 and discussed above ( Figure 7B,C) (49). Since rotation of Glu-272 away from the pocket is required to allow movement to the proximal domain, this would suggest that deprotonation of the semiquinone occurs before oxidation (after step c and before step d above), so that the semiquinone anion moves and donates to heme b L (steps d and e).…”
Section: Discussionmentioning
confidence: 98%
“…Earlier work from this lab had shown that the rate of quinol oxidation is determined by the probability of quinol binding, as shown by the secondorder nature of the reaction (15,21,50). We have more recently shown evidence that the oxidized ISP in its dissociated form reacts to form the complex and that the pH dependence of the rate in the acidic range reflects the availability of this species (41,42,49). Neither binding process contributes to the activation barrier, which is in the reactions after formation of the complex.…”
Section: Crofts Et Al Biochemistrymentioning
confidence: 96%
See 2 more Smart Citations
“…In a 1984 paper on this subject (Widger et al 1984b), which I was proud to have sponsored by Warren Butler, we noted the conserved PEWY (proline-glutamic acid-tryptophan-tyrosine) sequence, in which the E has subsequently been implicated in the lumen-side pathway of proton transfer from ubiquinol in the bacterial Cyt bc 1 complex (Crofts et al 1999). Given the apparent split of the 8 transmembrane helix mitochondrial Cyt b to a 4 helix Cyt b 6 and a 3-helix subunit IV, the questions were: (i) why was the apparently highly conserved mitochondrial and photosynthetic bacterial Cyt b gene divided in approximately half in oxygenic photosynthesis, where Cyt b 6 is the N-terminal half, the four helix heme-binding homologue of the mitochondrial cytochrome; (ii) was a relatively large 8-helix protein split into 2 fragments, subunit IV and Cyt b 6 (Widger et al 1984b), or were Cyt b 6 and subunit IV fused to form the 8-subunit Cyt b of the Cyt bc 1 complex (Schütz et al 1994)?…”
Section: Mechanism Of Action Of Oxygen Transportermentioning
confidence: 99%